The Effect of Coffe Pulp Fermented in Feed to Consumption and Body Weight Gain Etawa Crossbreed Goat - pinardi pinardi (Jurnal Sains Peternakan, 2015)
ABSTRACTThis research  aims to determine the effect of fermented  coffee pulp  within feed toward consumptions and body weight gain Etawa Crossbreed Goat (PE). Subject used in this research was 9 goats male Etawa Crossbreed Goat (PE) with a weight of 22-29 kg. The experimental method  in  this  research  consists  of  3  treatments  with  3  replications  livestock.  Control treatment P0 pollard 100%; P1 pollard 50% + KKF 50%; P2 pollard 40% + KKF 60%. The variables measured in this research are consumptions and body weight gain. The results of this research is the addition of KKF feed substitution within feed pollard do have significant effects (P<0.01) on consumptions and body weight gain. The average a high consumptions value P1 as consumptions BK (848.80) and body weight gain (133.33 g /head/day) the average, P0 as consumptions PK (105.29) the average, P2 as consumptions SK (205.64) the average. The researcher concludes that there was a significant effect of fermented coffee pulp within feed toward consumptions and body weight gain Etawa Crossbreed Goat (PE). Moreover, the researcher shows the addition of KKF feed substitution within feed pollard it can improve of PBB goats high of body weight gain (133 g/head/day). Keywords: Goats, Methods, Consumptions, Body Weight Gain.